2012
DOI: 10.1007/s00040-012-0252-8
|View full text |Cite
|
Sign up to set email alerts
|

Skewed soldier sex ratio in termites: testing the size-threshold hypothesis

Abstract: Social insect colonies contain multiple phenotypes, i.e. castes, and this caste polyphenism is often linked to sexual dimorphism. Unlike social hymenopterans, both termite sexes are diploid and contribute to helper-type tasks within the colony. Nonetheless, a biased sex ratio is frequently observed in termites, especially in soldiers. To explain this bias in soldier sex ratio, Matsuura (2006) postulated the existence of a size threshold for workers molting into soldiers. Under the influence of sexual size dimo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Sexual specialization in soldiers is a common feature in termites (Bourguignon, Hayashi, & Miura, ; Noirot, ). In species with phragmotic defence, in which soldiers use their large head as a plug to block the tunnels (Eggleton, ), a proposed hypothesis is that there is a size threshold below which workers cannot develop into soldiers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sexual specialization in soldiers is a common feature in termites (Bourguignon, Hayashi, & Miura, ; Noirot, ). In species with phragmotic defence, in which soldiers use their large head as a plug to block the tunnels (Eggleton, ), a proposed hypothesis is that there is a size threshold below which workers cannot develop into soldiers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, species with sexual size dimorphism (SSD) in the neuter castes should display a soldier sex ratio biased in favor of the larger sex (Matsuura, ). While this hypothesis holds for many lower termites, unisexual soldiers are common across Termitidae species that do not display SSD (Bourguignon et al, ). Accordingly, our results reveal an absence of sexual dimorphism in larvae and workers of C. tuberosus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bourguignon et al . () tested this hypothesis, and observed that while the hypothesis was held for many lower termite species, multiple species of Termitidae did not exhibit SSD but presented a highly skewed soldier sex ratio. This is the case for S. euamignathus .…”
Section: Discussionmentioning
confidence: 99%
“…In Reticulitermes speratus a sex-linked locus with two alleles is responsible for caste determination, where the same allele that causes males to develop into reproductives also causes females to develop into workers; whereas the other allele causes males to develop into workers and females to develop into reproductives (Hayashi et al , 2007). In a different study, it was suggested that termite species with greater levels of sexual size dimorphism tend to have workers of a single sex that are more specialised (Bourguignon, Yoshinobu & Miura, 2012). These examples suggest that sexual dimorphism might have enabled functional specialisation of worker castes, as predicted if mechanisms to resolve one conflict act to mitigate the other.…”
Section: Diversity Of Systems For Empirical Tests Of Caste Antagonismmentioning
confidence: 99%